THE Penambahan Traksi Maximaly Lose Pack Position Glenohumeral Pada Intervensi Micro Wave Diathermy Dan Ultrasound Mengurangi Nyeri Frozen Shoulder - Ngakan Nyoman Gde Sudarma (Majalah Ilmiah Fisioterapi Indonesia, 2013)
Frozen shoulder is a syndrome or condition with attacks of pain and active and passive motion limitation with an uncertain cause/ idiopathic. Frozen shoulder is a common cause of chronic pain and disability in the shoulder, but still much less understanding of movement disorders of the shoulder. The purpose of this study was to determine how much pain reduction effectiveness of the addition of MLPP glenohumeral traction on a combination of MWD and the US interventional to the patient's Frozen Shoulder. Experimental studies have been done with the design of randomized pre test and post test group design. Sample size of 28 is divided into two groups of 14 persons each. Treatment group I with the combination MWD and the US, while treatment group II with glenohumeral traction MLPP, MWD and the US. The data was collected by measuring the intensity of pain using the VAS, at the time before and after treatment, then performed with different test t test (paired t test and independent t test). The results showed there is significant effect of each treatment to decrease pain intensity p = 0.000 (p <0.05). But the average level of pain after treatment group II seems more effective to reduce pain. Giving traction on frozen shoulder glenohumeral MLPP will stimulate nociceptor to induce mechanoreseptor resulting in increased vascularity so slowly-the land will reduce pain. So it is advisable to add MLPP glenohumeral on a combination of MWD and the US to reduce pain in patients with frozen shoulder.